2016
DOI: 10.1259/bjr.20150966
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hypofractionated radiotherapy with concomitant chemotherapy in locally advanced squamous cell carcinoma of lung: evaluation of response, survival, toxicity and quality of life from a Phase II randomized study

Abstract: Cite this article as: Roy S, Pathy S, Mohanti BK, Raina V, Jaiswal A, Kumar R, et al. Accelerated hypofractionated radiotherapy with concomitant chemotherapy in locally advanced squamous cell carcinoma of lung: evaluation of response, survival, toxicity and quality of life from a Phase II randomized study. Conclusion:The study suggests that AHFx-RT-CT is feasible for locally advanced SCC of the lung with improved response rate, survival, QOL and favourable toxicity. Advances in knowledge: To the best of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Recently, several phase I and II clinical trials have been designed to combine chemotherapy with hypofractionated radiotherapy (HYPO-RT) to intensify radiotherapy in a different way (13)(14)(15). These studies have demonstrated that irradiation delivered within a short period (4 or 5 weeks) and at a radiation dose of ≥2.5 Gy per fraction combined with chemotherapy is feasible and shows encouraging outcomes (13)(14)(15). The rationale supporting CRT with HYPO-RT is to limit tumor repopulation and enhance local control with consequent survival improvement (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several phase I and II clinical trials have been designed to combine chemotherapy with hypofractionated radiotherapy (HYPO-RT) to intensify radiotherapy in a different way (13)(14)(15). These studies have demonstrated that irradiation delivered within a short period (4 or 5 weeks) and at a radiation dose of ≥2.5 Gy per fraction combined with chemotherapy is feasible and shows encouraging outcomes (13)(14)(15). The rationale supporting CRT with HYPO-RT is to limit tumor repopulation and enhance local control with consequent survival improvement (16,17).…”
Section: Introductionmentioning
confidence: 99%